2019
DOI: 10.1590/0034-7167-2018-0378
|View full text |Cite
|
Sign up to set email alerts
|

Generating situations of Moral Distress in Primary Care Nurses

Abstract: Objective: To analyze the situations generating Moral Distress in Primary Care nurses from different regions of Brazil. Method: Qualitative research, with 13 nurses of the Brazilian Primary Health Care, through a semi-structured interview and submitted to the Discursive Textual Analysis, with the resources of the software ATLAS.ti 7.0. Results: They are presented in four categories, relating the Moral Distress to the professional; health services; users and conflicts in professional practice. Final Consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
1
10
0
2
Order By: Relevance
“…Many factors trigger moral distress in nurses, many of which are related to everyday life, such as poor organization of the working process; conflicting interpersonal relationships among the patient, the community, and the healthcare professionals; controversial management of the ruling system and services provided [ 25 , 32 ]. Barth et al [ 25 ] also identified “lack of qualification of the professional himself”, explained by the contrasting evolution of primary care systems and settings. This is confirmed by findings from Burston et al [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors trigger moral distress in nurses, many of which are related to everyday life, such as poor organization of the working process; conflicting interpersonal relationships among the patient, the community, and the healthcare professionals; controversial management of the ruling system and services provided [ 25 , 32 ]. Barth et al [ 25 ] also identified “lack of qualification of the professional himself”, explained by the contrasting evolution of primary care systems and settings. This is confirmed by findings from Burston et al [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority (n = 7) of the studies were qualitative in design [19][20][21][22][23][24][25]: three studies were quantitative [26][27][28], three were validation studies [29][30][31], one study was an integrative review [32], and one was a case study [33].…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…Somando barreiras culturais, dificuldade de acesso aos serviços, sobrecarga de trabalho vivenciada pelos profissionais e carência de inovação às adversidades atreladas ao tratamento proposto, totalizam obstáculos sociais/organizacionais de complicada resolução. A falta de continuidade do cuidado, articulada a problemas relacionados aos encaminhamentos e a organização de fluxos reforça a vulnerabilidade do usuário e do próprio profissional (Barth et al, 2019).…”
Section: Discussionunclassified
“…The studies on moral distress in the field of nursing, especially in the last five years and also in Brazilian settings, have pointed out several generating situations or risk factors, strongly associated with the environment, including the structure and organization of the work process, as well as such as interpersonal relationships that are established (9)(10)(11)(12)(13) . After decades of studies, it is confirmed that the necessary and sufficient conditions to define moral suffering refer to the combination of the experience of a moral event and psychological suffering, in a direct causal relationship.…”
Section: Introductionmentioning
confidence: 99%